Retina and microvascular alterations in migraine: a systemic review and meta-analysis - Liu, Ziqiang; Jie, Chuanhong; Wang, Jianwei; Hou, Xiaoyu; Zhang, Weiqiong; Wang, Jingying; Deng, Yu; Li, Yuanyuan (Frontiers in Neurology, 2023)
Objective: To evaluate the retina and microvascular alterations with optical coherence tomography (OCT) or optical coherence tomography angiography (OCTA) in patients with migraine with aura (MA) and migraine without aura (MO).Methods: PubMed, Embase, and Cochrane Library databases were searched to find relevent literature on patients with MA or MO using OCT/OCTA devices. The eligible data were analyzed by Stata Software (version 15.0).There were 16 studies identified, involving 379 eyes with MA, 583 eyes with MO, and 658 eyes of healthy controls. The thickness of the peripapillary retinal nerve fiber layer (pRNFL) of patients with MA decreased significantly in most regions. The foveal avascular zone (FAZ) area and perimeter in MA patients significantly enlarged, while the perfusion density (PD) in the macular deep capillary plexus (mDCP) significantly decreased in the whole image and its subregions except for the fovea, with the PD in radial peripapillary capillary (RPC) decreasing inside the disc. Patients with MO demonstrated a significantly decreased thickness of pRNFL in most regions, and the FAZ parameters were significantly enlarged. No statistical significance was observed in the retina and microvascular features of patients with MA and MO.The eyes affected by MA and MO demonstrated significantly reduced thickness of pRNFL and enlarged FAZ. Patients with MA showed retinal microvascular impairments, including a decreased PD in mDCP. The OCT and OCTA could detect membrane morphology and circulation status in migraine and might provide the basis for the diagnosis and follow-up of patients with migraine.